Maternal physical-activity-related parenting behaviors may influence children's physical activity levels and relative weight. - Rosenkranz, Richard R.; Dzewaltowski, David A. (My University, 2011)
Previous studies have demonstrated that parents may influence the physical activity (PA) levels of children. The present study sought to determine whether PA-related parenting behaviors were associated with the physical activity and relative weight of children, controlling for other covariates. A community sample of mothers (n = 193) of after-school-program attendees completed questionnaires assessing parental social support for PA, sedentary behavior, and moderate-to-vigorous physical activity. Children (N = 193, 51% girls) were objectively assessed for height and weight via stadiometer and digital scale, and the date were converted to body mass index (BMI) percentile via Centers for Disease Control and Prevention (CDC, 2010a) growth charts. Linear regression analysis revealed that maternal encouragement for child PA was positively related to both child PA and BMI percentile. However, mother,child shared physical activity was negatively related to child BMI percentile. Therefore, varying types of PA-related parenting behaviors may have differential relationships with child PA and relative weight.
Keywords: Physical activity; Parenting behaviors; Mother child influence; Children's physical activity; Children's BMI percentile